2015
DOI: 10.1111/hpb.12501
|View full text |Cite
|
Sign up to set email alerts
|

Improved liver function after portal vein embolization and an elective right hepatectomy

Abstract: For equivalent volumes, the immediate post-operative hepatic function appears to be better in livers prepared with PVE than in unprepared livers. Future studies should analyse whether the conventional inferior volume limit that allows a safe liver resection may be lowered when a PVE is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Meier et al. , interestingly, demonstrated that preoperative PVE positively influenced postoperative liver function independently from changes expected from increase in liver volume alone, suggesting that PVE not only increases the postoperative volume but also the functional capacity of the FRL.…”
Section: Resultsmentioning
confidence: 99%
“…Meier et al. , interestingly, demonstrated that preoperative PVE positively influenced postoperative liver function independently from changes expected from increase in liver volume alone, suggesting that PVE not only increases the postoperative volume but also the functional capacity of the FRL.…”
Section: Resultsmentioning
confidence: 99%
“…It is very important to figure out what is the mechanism of the regenerative ability of the liver after PVE, especially the relation between liver function improvement and liver volume increment. Meier et al[ 56 ] retrospectively compared post-right hepatectomy outcomes in 28 patients with and 53 without PVE in a non-randomized study, suggesting that the immediate post-operative liver function per unit of volume in patients with PVE was better than those without PVE. This finding was also similar to Farges et al[ 47 ] who found the improved post-operative liver function in patients with PVE compared with those without PVE in terms of the chronic liver.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative portal vein embolization (PVE) before hepatice resection has been widely applied to induce the hypertrophy of FLR for patients undergoing a major resection 2 . Sequential preoperative TACE and PVE before major hepatic resection have been shown to strengthen the effect of PVE and simultaneously prevent tumor progression during the waiting time 3 . In recent years, the associating liver partition with portal vein ligation for staged hepatectomy (ALPPS) has been proposed as a novel approach to induce the rapid liver regeneration, resulting in increasing the chance of resectability 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Resection options are often limited by a reduced hepatic reserve. With recent advances of perioperative management and surgical techniques, hepatic resection has been performed safely for selected patients with large HCC 3, 4. For those patients with large HCC who can be resected, the overall survival has been shown to be better than the nonsurgical treatment 5 …”
Section: Introductionmentioning
confidence: 99%